Karlheinz Kessler. Del curriculum profesional y las circunstancias vitales de un sabio alemán - Kessler, Dieter; Müller-Kressler, Christina (ISIMU, 2019)
Karlheinz Kessler. Del curriculum profesional y las circunstancias vitales de un sabio alemán